Equipment reservation system (EQUIPRES) / Nor Fadhilah Ismail - Ismail, Nor Fadhilah (2013)
Web-based applications are programs that run on Web servers and use Web pages as the user interface. The application usage of Internet website and online reservation system are currently dominating the modern information technology which gives many advantages to people. For that reasons, the project entitled “EQUIPRES” web based system is developed to ease applicant in making equipment reservation process and administrator to manage equipment reservation for InfoTech UiTM Terengganu. This project is developed using Model View Controller approach. Model View Controller approach, which is design pattern for computer user interfaces applied in web based system design. It divides an application into three areas of responsibility Model, View, and Controller. Reservation system EQUIPRES enables the applicant to register their account, update their profile and make equipment reservation. Besides that, the administration can add staffs, equipment, approve the equipment reservation as well as updating and deleting the records information. This project also will create paperless environment and save time applicant and InfoTech staff to making equipment reservation. Therefore, the interface design and functionality of the EQUIPRES web based system need to be improved.